Menyoal Seni Lukis Indonesia Kini - -, Dharsono (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2009)
Our painting trip since pioneering R. Saleh until the beginning of this XXI, was still swayed by the impact of conception. Indonesian art esta-blishment that has not reached the level of success, it has been devastating by western modernism that produce alternative art, with the emergence of the concept art (art conseptual): "Installation Art", and "Performance Art", which once flourished in college campuses throughout the art of the late 20th century. Then came the various alternatives such as "collaboration" as the final mode. Along the same conventions of painting adorned with a variety of styles-galleries, which is no longer as a token of appreciation to the community, but an alternative investment business. Now (the early 21st century) painting exposed to two forces; art remains a classic value of conventional forces from the inner consumption that belonged to the community, cha-llenged by the phenomenon of art as a market management forces in berorentasi leading commercial value in popular culture. Art no longer belongs to the people ....... Keyword: arts, painting, popular culture